Galician Associations and the Publishing Industry in Buenos Aires in Mid-Century: Two Publishing Projects by Luís Seoane - Gerhardt, Federico (Madrygal. Revista de Estudios Gallegos, 2015)
Analysis of two publishing projects written by Luis Seoane, during a rise in the book market in Argentina and the development of the Galician associations in Buenos Aires. Firstly, the project of “Biblioteca de Autores Gallegos” of Losada and Centro Gallego (1939). Secondly, the project to create Ediciones del Centro Lucense (1950).